Severe fatty liver disease and acute pancreatitis: is there a correlation between them? - Qi, Xingshun (Clin Exp Hepatol, 2016)
In this manuscript, we present two cases of patients with severe fatty liver disease developing acute pancreatitis. They might suggest an association between severe fatty liver disease and acute pancreatitis.